PtNi-W/C with Atomically Dispersed Tungsten Sites Toward Boosted ORR in Proton Exchange Membrane Fuel Cell Devices - Wang, Huawei; Gao, Jialong; Chen, Changli; Zhao, Wei; Zhang, Zihou; Li, Dong; Chen, Ying; Wang, Chenyue; Zhu, Cheng; Ke, Xiaoxing; Pei, Jiajing; Dong, Juncai; et al. (Nano-Micro Letters, 2023)
The performance of proton exchange membrane fuel cells is heavily dependent on the microstructure of electrode catalyst especially at low catalyst loadings. This work shows a hybrid electrocatalyst consisting of PtNi-W alloy nanocrystals loaded on carbon surface with atomically dispersed W sites by a two-step straightforward method. Single-atomic W can be found on the carbon surface, which can form protonic acid sites and establish an extended proton transport network at the catalyst surface. When implemented in membrane electrode assembly as cathode at ultra-low loading of 0.05 mgPt cm−2, the peak power density of the cell is enhanced by 64.4% compared to that with the commercial Pt/C catalyst. The theoretical calculation suggests that the single-atomic W possesses a favorable energetics toward the formation of *OOH whereby the intermediates can be efficiently converted and further reduced to water, revealing a interfacial cascade catalysis facilitated by the single-atomic W. This work highlights a novel functional hybrid electrocatalyst design from the atomic level that enables to solve the bottle-neck issues at device level. Highlights: 1 A hybrid electrocatalyst consisting of PtNi-W alloy nanocrystals loaded on carbon surface with atomically dispersed W sites was realized. 2 Single-atomic W formed protonic acid sites and established an extended proton transport network at the catalyst surface. 3 Peak power density is enhanced by 64.4% compared to that with the commercial Pt/C catalyst in fuel cell as cathode at ultra-low loading of 0.05 mgPt cm−2.